A Slovene-English contrastive analysis of one - Kocijančič-Pokorn, Nike (Slovenski jezik, 1997)
The article attempts to determine whether there exist any regular equivalents in Slovene corresponding to English one, which could help translators from or into English in their work. On the basis of an analysis of three original texts (two English and one Slovene) and five translations (four into Slovene and one into English), several translational equivalents to various functions of one are proposed.
Keywords: angleščina; English; kontrastivna analiza; linguistics; lingvistika; prevajanje; Slovene; slovenščina; translation